Ultra-Wideband Ultra-Thin Transmissive Linear to Circular Polarization Convertor Based on Crossed-Dipole-Shaped Metasurface - Hilary Scott Nkimbeng, Cho; Wang, Heesu; Yoon, Daeyeong; Yong Bae, Park; Han, Haewook; Park, Ikmo (IEEE Access, 2024)
This paper presents an ultra-thin, ultra-wideband linear-to-circular (LTC) polarization converter based on the crossed-dipole-shaped metasurface. The unit cell of the crossed-dipole-shaped metasurface is made up of two identical T-shaped dipole arms, which are orthogonal to each other and are connected with a diagonal microstrip line. The LTC polarization converter is placed on the top side of an ultra-thin single-substrate layer with a profile size of 0.035λo , where λo is a free space wavelength at the center frequency of the axial ratio bandwidth (20.89 GHz). The proposed design shows nearly equal transmission amplitude and stable phase difference of nearly 90° of the two orthogonal components of transmitted waves in a wide frequency range. The right-hand circularly polarized (RHCP) component of the transmitted wave is much larger than the left-hand circularly polarized, and thus, the transmitted wave is RHCP. Numerical and experimental results showed that the polarizer could realize an ultra-wideband LTC polarization conversion at both x- and y-polarized incidences in the frequency range from 11.66 to 30.12 GHz, which is a fractional bandwidth of 88.4%, and it can maintain a stable polarization conversion performance under large-range incidence angles. In addition, a high total transmittance of the electromagnetic wave was obtained.
Keywords: Crossed dipoles; Linear polarization; Linear-to-circular polarization converter; Metasurface; Polarization converters; Thermal; Transmission coefficients; Ultra-wideband technology; Ultrawide band; Wide-band; Circular polarization; crossed-dipole; linear polarization; linear-to-circular polarization converter; transmission coefficient; ultra-wideband